2016
DOI: 10.1017/s1355617716000692
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption Does not Impede Recovery from Mild to Moderate Traumatic Brain Injury

Abstract: Alcohol may not significantly alter long-term outcome from mild to moderate TBI. (JINS, 2016, 22, 816-827).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…For more details of the participant selection process and exclusion criteria see Silverberg et al. (2016). A flow‐chart describing the selection process is available in the Supporting Information as Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…For more details of the participant selection process and exclusion criteria see Silverberg et al. (2016). A flow‐chart describing the selection process is available in the Supporting Information as Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…For example, one study showed that preinjury, acute alcohol intoxication, and postinjury alcohol use did not influence symptom severity or neurocognitive outcomes a year after mild-to-moderate TBI. 19 Another showed that postinjury alcohol use did not affect postconcussion symptom scores 4 weeks after injury. 21 Similar to our study, these findings were limited by recall bias and self-reported symptom scores.…”
Section: Discussionmentioning
confidence: 99%
“…Some have shown that alcohol use after mild or moderate TBI improves or has no effect on recovery outcomes. [19][20][21] Others suggest that alcohol consumption can worsen outcomes after TBI. 22,23 For example, alcohol consumption (primarily in patients with chronic alcohol use and/or acute intoxication) has been associated with longer episodes of posttraumatic amnesia, alterations in cerebral metabolism, [24][25][26] brain atrophy on magnetic resonance imaging, and difficulty with learning and memory after TBI with varying degrees of severity (mild, moderate, and severe).…”
Section: Introductionmentioning
confidence: 99%